Relationships between age of females and attraction to the Dark Triad personality. (June 2016) - Qureshi, Corinne; Harris, Elizabeth; Atkinson, Breanna E.
Abstract: The current study extended previous literature that had investigated the attractiveness of the Dark Triad (DT) personality to youthful women (Carter, Campbell, & Muncer, 2014), by comparing responses between two age groups. Participants ( N  = 1001 females) consisted of undergraduate students and women sampled from various North American communities. Participants read descriptions of male personalities and rated their attractiveness. Descriptions of male characters were designed to portray a combination of high scores on the Dark Triad traits (Machiavellianism, narcissism, and sub-clinical psychopathy), and results were compared to ratings on a low-scoring DT personality. Results were generally supportive of the hypotheses, such that younger women were more attracted to the Dark Triad traits than were older women; older women also rated the low-scoring DT personality as significantly more attractive than did younger women. However, inconsistent with previous literature, younger women rated the low-scoring DT personality as significantly more favorable than the high-scoring DT personality. Further, the participants' level of fertility did not significantly influence attractiveness ratings. The current study's findings may deepen understanding of the ways in which mating strategies change with age, as well as the qualities that women desire in a mate, in order to improve mating success. Highlights: Designed characters high and low on the Dark Triad Measured attractiveness ratings of these characters Compared younger and older women's attractiveness ratings Younger women are more attracted than older women to high Dark Triad character Older women more attracted to low than to high Dark Triad character